ANALISIS PENGEMBANGAN USAHA LEPAT BUGI DI KECAMATAN TAMBANG KABUPATEN KAMPAR - Mifta Fishah; Jahrizal '; Taryono ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Lepat Bugi is one of the traditional foods are on the road cross Pekanbaru Bangkinang precisely in the District Mine Kampar regency. The theory used in this research is the theory of Michael Porter (five force model). The purpose of this study was to determine, knowing the variables that influence the development of the industry in the District Mine Lepat Bugi. Knowing how the condition scale production (Return to Scale) industry in Sub Mine Lepat Bugi. Knowing the efficiency of use of factors of industrial production for the Lepat Bugi in DistrictMine. The results of this study indicate that the variable is the supplier of the most influential variables, namely in terms of labor and raw materials. While the scale of production results show increasing returns to scale, meaning that the proportion of additional production will be greater than the proportion of the addition of production inputs. whereas the efficiency of capital is equal to 0.691, which means not efficient. as well as labor efficiency is 0.199 which shows yet efficient.Keywords: capital , labor , return to scale , and efficiency